(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2016)
The paper analyzes the presence and the geographical distribution of real estate confiscated assets from organized crime. Using data made available by The National Agency of Confiscated Property and Libera association, it provides a quantitative analysis integrated with a qualitative approach on the field with the purpose to highlight examples of best practices in the social re-use of these confiscated assets. In this qualitative analysis are also taken into account some key indicators: the asset’s structural features, its relationship with memory, its public reputation and the activities made inside it. Finally, it emerges a Lombard model of social reuse marked by some interesting criticalities. Key words: Confiscated property, Lombardy, Social business, Best practices, Memory